“TABAH DI DALAM KEKURANGANKU” Studi Kualitatif Mengenai Hardiness pada Individu Dewasa Madya Penyandang Tunadaksa yang Bekerja - Muhammad Idham Abiyoga; Dian Ratna Sawitri (Jurnal EMPATI, 2017)
This research is a qualitative research with a phenomenology perspective that aims to know the hardiness of the mature adult individuals who work with the disabled. Subjects in this study amounted to three people taken with purposive technique. Data collection was done by interview method. Interviews indicated that the three subjects had hardiness personality in work developed in different ways depending on the background of disability acquired as newly born or as adults. Personality hardiness subject number 1 who experienced disability due to fire, developed because of responsibility to the family. The desire to live independently makes subject number 2 has a hardiness personality. The gratitude and support of the people around make the subject number 3 can develop hardiness personality.